Asosiasi Gastropoda Inter-Spesies Pada Habitat Lamun Di Perairan Desa Tayando Yamtel Kecamatan Tayando Tam Kota Tual - gea, liyatin (Biosel Biology Science and Education, 2022)
The gastropod community is an important component in the food chain in seagrass beds, where gastropods are basic detritus feeders. Research on gastropod associations in seagrass habitats in the waters of Tayando Yamtel Village, Tam District, Tual City, was carried out in March-May 2018, using the quadrant linear transect method. Based on the results of the research on gastropod association patterns (inter-species) in the waters of Tayando Yamtel Village, the two species formed 435 pairs, namely 158 species pairs that were positively associated, 91 species pairs that were negatively associated and 186 pairs of species that were not associated. With high and very high association index values, reaching 56.091% and low and very low association index values, reaching 43.909%. Meanwhile, the gastropod association between all species based on the association index value can be concluded that the association relationship is negative. Keywords: Association, Gastropods, Tayando Yamtel